2020
DOI: 10.1515/opag-2020-0088
|View full text |Cite
|
Sign up to set email alerts
|

Is organic agriculture a potential public health indicator? Evidence from literature

Abstract: Organic agriculture is a system of production whose principles are health, ecology, fairness, and care. Bearing in mind the principle of health and its links to agriculture and human health, the main goal of this work is to suggest the inclusion of organic agriculture as a public health indicator. For this purpose, four scientific online databases such as b-on, PubMed®, Scielo, and ScienceDirect were used for searching the research publications relating organic agriculture (and organic farming) with human heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
1
1
0
1
Order By: Relevance
“…Most participants in both groups showed the willingness to consume organic food, justified by the perception that the environment and one's health would be protected. This finding is aligned with several studies conducted in other countries (Ben Hassine et al, 2014;Andersen et al, 2015;Ferreira et al, 2020;Tandon et al, 2020). As expected, the tendency to translate this willingness into the action of consuming organic products was prevalent in the "organic group. "…”
Section: Consumer Behaviorssupporting
confidence: 90%
“…Most participants in both groups showed the willingness to consume organic food, justified by the perception that the environment and one's health would be protected. This finding is aligned with several studies conducted in other countries (Ben Hassine et al, 2014;Andersen et al, 2015;Ferreira et al, 2020;Tandon et al, 2020). As expected, the tendency to translate this willingness into the action of consuming organic products was prevalent in the "organic group. "…”
Section: Consumer Behaviorssupporting
confidence: 90%
“…A crescente preocupação sobre o modo de produção por parte dos diversos atores da sociedade, tem vindo a contribuir para o aumento da área de produção e dos investimentos realizados em Portugal, no que diz respeito à área destinada à agricultura biológica (58). Recentemente, foi apresentada uma proposta de modelo pictórico representando a interligação entre a agricultura biológica, a sustentabilidade (social, económica e ambiental) e a saúde pública, questionando a possibilidade de, no futuro, a agricultura biológica poder vir a ser considerada um potencial indicador de saúde pública (59).…”
Section: Alimentação Baseada Em Plantas E Sustentabilidadeunclassified
“…This works under the four principles: health, care, fairness, and ecology (IFOAM, 2020). A wide range of studies has demonstrated the advantageous aspects of OF in terms of ecosystem functioning, soil fertility conservation, and economic impact (Ferreira et al, 2020). According to Adamchak (2021), the concept of OF practices refers to an organic farm as an organism in which all the component parts (the soil minerals, plants, organic matter, micro-organisms, insects, and animals, including humans) interact to create a coherent and stable whole.Statistics by Food and Agriculture Organization (FAO) found that there are more than 608 million farmers around the world involved in OF (FAO, 2021).…”
mentioning
confidence: 99%